2013
DOI: 10.1161/hypertensionaha.111.00098
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Insulin Action of Adding Low-Dose Thiazide to Angiotensin-Converting Enzyme Inhibitor in Essential Hypertension

Abstract: Abstract-Concern exists regarding adverse metabolic effects of antihypertensive agents. In the United States, diuretics are recommended first-line but additional agents, usually angiotensin-converting enzyme (ACE) inhibitors, are often required to meet blood pressure targets. We have previously shown that the combination of low-dose diuretic with an ACE inhibitor has detrimental effects on insulin action compared with ACE inhibitor alone in hypertensive type 2 diabetic patients. Our aim was to establish whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…In summary, the use of thiazides has been clearly linked to new-onset diabetes in clinical trials and impairments in insulin sensitivity, especially in those at increased risk such as overweight, hypertensive individuals, as seen in the current study (7). While these observational results from a relatively small cohort should be viewed cautiously, the use of mechanistic clamp studies in larger cohorts will be necessary to help elucidate the pancreatic beta cell and insulin sensitive tissue effects of diuretics and/or RAAS blockers.…”
supporting
confidence: 51%
See 2 more Smart Citations
“…In summary, the use of thiazides has been clearly linked to new-onset diabetes in clinical trials and impairments in insulin sensitivity, especially in those at increased risk such as overweight, hypertensive individuals, as seen in the current study (7). While these observational results from a relatively small cohort should be viewed cautiously, the use of mechanistic clamp studies in larger cohorts will be necessary to help elucidate the pancreatic beta cell and insulin sensitive tissue effects of diuretics and/or RAAS blockers.…”
supporting
confidence: 51%
“…In this issue of Hypertension , McHenry et al (7) build upon their previous work (8) exploring the addition of an ACEi captopril to bendrofluazide and utilizing hyperinsulinemic, euglycemic clamps to evaluate insulin sensitivity. The authors utilized a prospective randomized, cross-over design with a 6 week wash-in followed by 12 weeks of treatment in each arm with clamp studies to evaluate glucose disposal and endogenous glucose production as a marker of hepatic insulin sensitivity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One study has shown that low-dose addition of thiazide diuretic to ACEI therapy does not have a significant effect on insulin action and hence on the glucose turnover in the body. This study suggested that the use of thiazides in low doses is safe [39]. The retrospective longitudinal cohort study on seven antihypertensive drug classes (ACEIs, ARBs, CCBs, diuretics, β-blockers, α-blockers, and vasodilators) demonstrated the independent association of diuretics, β-blockers, and calcium channel blockers with increased risk of NOD, whereas ACEIs, ARBs, α-blockers, and vasodilators were not associated with the risk of NOD [40].…”
Section: Antihypertensive Therapy and Incident Diabetesmentioning
confidence: 72%